2021
DOI: 10.1177/03128962211037772
|View full text |Cite
|
Sign up to set email alerts
|

Abusive supervision, occupational well-being and job performance: The critical role of attention–awareness mindfulness

Abstract: Drawing from the job demands–resources (JD-R) model, this study sets out to investigate two complementary mechanisms that underpin the connection between employees’ exposure to abusive supervision and diminished job performance – one that is health-related (higher emotional exhaustion) and another that is motivation-related (lower work engagement). It also examines how this harmful process might be contained by employees’ mindfulness, particularly as manifest in its attention–awareness component. Data collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 111 publications
(220 reference statements)
0
4
0
Order By: Relevance
“…(2021) found psychological capital as the mediator between abusive supervision and sub-optimal outcomes. De Clercq et al. (2021) contended emotional exhaustion and work engagement are the mediators between abusive supervision and job performance.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) found psychological capital as the mediator between abusive supervision and sub-optimal outcomes. De Clercq et al. (2021) contended emotional exhaustion and work engagement are the mediators between abusive supervision and job performance.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with prior research (e.g. De Clercq et al. , 2022), if two respondents reported to the same supervisor (which was uncommon), we asked the supervisor to forward one survey to a colleague who was familiar with the work efforts of one of these respondents and who had not completed any other employee survey.…”
Section: Methodsmentioning
confidence: 97%
“…Studies on the impact of abusive supervision on employees' behavior have shown that subordinates deal with the sense of injustice caused by humiliation and abuse by reducing their own resources. For example, employees will reduce their pro-organizational behavior [18], OCB [9][10][11][12], and voice behavior [19], consequently depreciating their work performance [9,20,21]. Mitchell and Ambrose [22] have found that employees suffering from abusive supervision may choose to directly retaliate against their supervisors, causing supervisor-oriented workplace bias behavior, or motivate their colleagues to retaliate against the organizations' members or other colleagues, inducing organization-oriented and interpersonal-oriented workplace bias behaviors.…”
Section: Abusive Supervisionmentioning
confidence: 99%